2017
DOI: 10.1039/c7cc02842c
|View full text |Cite
|
Sign up to set email alerts
|

CO-Induced apoptotic death of colorectal cancer cells by a luminescent photoCORM grafted on biocompatible carboxymethyl chitosan

Abstract: A photo-active luminescent rhenium carbonyl complex namely, [Re(CO)3(phen)(pyAl)](CF3SO3) was grafted on a biocompatible carboxymethyl chitosan (CMC) matrix through Schiff base condensation reaction. The light-induced CO delivery from ReCMC has been shown to eradicate human colorectal adenocarcinoma cells (HT-29) very efficiently in a dose-dependent fashion. The onset of CO-induced apoptosis was realized by caspase-3,-7 detection aided by fluorescence confocal microscopy. ReCMC represents a unique example of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…In the absence of illumination to induce CO release, complex 4 shows no apparent cellular toxicity. However, a dose dependent eradication of HT‐29 cells was observed upon UV light‐induced CO release …”
Section: Luminescent Metal Carbonyl Co‐releasing Molecules and Their mentioning
confidence: 99%
See 3 more Smart Citations
“…In the absence of illumination to induce CO release, complex 4 shows no apparent cellular toxicity. However, a dose dependent eradication of HT‐29 cells was observed upon UV light‐induced CO release …”
Section: Luminescent Metal Carbonyl Co‐releasing Molecules and Their mentioning
confidence: 99%
“…No cytotoxicity data were reported for 1–3. Complex 4, [Re(CO) 3 (phen)(pyAl)]O 3 SCF 3 (where pyAl=pyridine‐4‐carboxaldehyde), which was grafted on to a biocompatible carboxymethyl chitosan (CMC) matrix, was found to be taken up by MDA‐MB‐231 breast cancer cells and HT‐29 colon cancer cells as evidenced by intracellular emission at 550 nm . In the absence of illumination to induce CO release, complex 4 shows no apparent cellular toxicity.…”
Section: Luminescent Metal Carbonyl Co‐releasing Molecules and Their mentioning
confidence: 99%
See 2 more Smart Citations
“…1 In recent years, exogenous delivery of CO has shown promise as a novel therapeutic in a variety of disease and injury models, including cancer. 2 The challenge of delivering efficacious concentrations of CO to a target tissue has been approached by our group and others by synthesizing CO-releasing molecules (CORMs) with properties necessary for a potential therapeutic, including water solubility, 3 incorporation within biocompatible materials 4,5 and controllable release of CO. [6][7][8][9] Very recently, with the use of photoactivatable CORMs (photoCORMs) our group has elucidated mechanism(s) by which CO exerts deleterious effects against human breast and ovarian cancer cell models. 10,11 In such studies we have observed sensitization of ovarian cancer cells to drugs like cisplatin and paclitaxel through coadministration of CO. 11 Because sensitization to conventional chemotherapeutics could mitigate the poor outcome of ovarian cancer treatment, precise target-specic delivery of CO to the malignant tissue appears to be a very desirable goal.…”
Section: Introductionmentioning
confidence: 99%